PENGARUH SIKAP SKEPTIS, INDEPENDENSI, PENERAPAN KODE ETIK, DAN AKUNTABILITAS TERHADAP KUALITAS AUDIT - Nandari, Ade Wisteri Sawitri; Latrini, Made Yenni (E-Jurnal Akuntansi; Vol 10 No 1 (2015), 2015)
The auditor will be able to result a report that has a good quality with attitude skepticism and independent attitude in the examination of financial statements. It is based on the application of the code of ethics  public accountant as a basic principles that govern the ethics of public accounting profession, besides that the accountability can make the auditor will be able to improve the quality of his work. This research is used to determine the effect of Attitude Skepticism, Auditor Independence, Application of the Code of Public Accountants, and Accountability on the Quality Audit. The data used in this study is primary data obtained by distributing questionnaires to selected respondents. The data then processed by tabulation based on the answers to the questionnaire are purposive sampling qualified. The analysis used in this study through multiple regression analysis. The results of the study showed that skeptical attitude has no effect on audit quality. Auditor independence also had  no effect on audit quality. Application of the code of public accountants has a positive effect on audit quality, while accountability has no effect on audit quality. To produce a good quality audit, it is important for the public accountant to apply the code of ethics public accountant to be able to increase the confidence of users of financial statements.
Keywords: Skeptical Attitude, Independence, Code of Public Accountants, Accountability and Audit Quality